Prevalence of Oral HPV Infection in the United States, 2009-2010 - Gillison, Maura L; Broutian, Tatevik; Pickard, Robert K. L; Tong, Zhen-yue; Xiao, Weihong; Kahle, Lisa; Graubard, Barry I; Chaturvedi, Anil K (JAMA : the journal of the American Medical Association, 2012)
CONTEXT Human papillomavirus (HPV) infection is the principal cause of a distinct form of oropharyngeal squamous cell carcinoma that is increasing in incidence among men in the United States. However, little is known about the epidemiology of oral HPV infection. OBJECTIVE To determine the prevalence of oral HPV infection in the United States. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study was conducted as part of the National Health and Nutrition Examination Survey (NHANES) 2009-2010, a statistically representative sample of the civilian noninstitutionalized US population. Men and women aged 14 to 69 years examined at mobile examination centers were eligible. Participants (N = 5579) provided a 30-second oral rinse and gargle with mouthwash. For detection of HPV types, DNA purified from oral exfoliated cells was evaluated by polymerase chain reaction and type-specific hybridization. Demographic and behavioral data were obtained by standardized interview. Statistical analyses used NHANES sample weights to provide weighted prevalence estimates for the US population. MAIN OUTCOME MEASURES Prevalence of oral HPV infection. RESULTS The prevalence of oral HPV infection among men and women aged 14 to 69 years was 6.9% (95% CI, 5.7%-8.3%) and of HPV type 16 was 1.0% (95% CI, 0.7%-1.3%). Oral HPV infection followed a bimodal pattern with respect to age, with peak prevalence among individuals aged 30 to 34 years (7.3%; 95% CI, 4.6%-11.4%) and 60 to 64 years (11.4%; 95% CI, 8.5%-15.1%). Men had a significantly higher prevalence than women for any oral HPV infection (10.1% [95% CI, 8.3%-12.3%] vs 3.6% [95% CI, 2.6%-5.0%], P < .001; unadjusted prevalence ratio [PR], 2.80 [95% CI, 2.02-3.88]). Infection was less common among those without vs those with a history of any type of sexual contact (0.9% [95% CI, 0.4%-1.8%] vs 7.5% [95% CI, 6.1%-9.1%], P < .001; PR, 8.69 [95% CI, 3.91-19.31]) and increased with number of sexual partners (P < .001 for trend) and cigarettes smoked per day (P < .001 for trend). Associations with age, sex, number of sexual partners, and current number of cigarettes smoked per day were independently associated with oral HPV infection in multivariable models. CONCLUSION Among men and women aged 14 to 69 years in the United States, the overall prevalence of oral HPV infection was 6.9%, and the prevalence was higher among men than among women. JAMA. 2012;307(7):693-703 Published online January 26, 2012. doi:10.1001/jama.2012.101www.jama.com